2009
DOI: 10.1002/jcb.22207
|View full text |Cite
|
Sign up to set email alerts
|

Nit1 and Fhit tumor suppressor activities are additive

Abstract: The Fragile Histidine Triad gene (human FHIT, mouse Fhit) has been shown to act as a tumor suppressor gene. Nit1 and Fhit form a fusion protein, encoded by the NitFhit gene in flies and worms, suggesting that mammalian Nit1 and Fhit proteins, which are encoded by genes on different chromosomes in mammals, may function in the same signal pathway(s). A previous study showed that Nit1 deficiency in knockout mice confers a cancer prone phenotype, as does Fhit deficiency. We have now assessed the tumor susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…S12). Overall, this double localization of Nit1 is in agreement with the results of earlier studies (23,29) and is consistent with a role of the enzyme in recycling a side product of transaminases, which are abundant in both the cytosol and the mitochondria.…”
Section: Nit1 Localizes In Both the Cytosol And The Mitochondria Of Msupporting
confidence: 92%
“…S12). Overall, this double localization of Nit1 is in agreement with the results of earlier studies (23,29) and is consistent with a role of the enzyme in recycling a side product of transaminases, which are abundant in both the cytosol and the mitochondria.…”
Section: Nit1 Localizes In Both the Cytosol And The Mitochondria Of Msupporting
confidence: 92%
“…Previous studies showed that Fhit knockout mice are more sensitive than wt mice to carcinogen‐induced epithelial tumors of the forestomach and esophagus 14, 26. Therefore, we expected that Fhit − / − mice would also develop more NMSC tumors compared to wt B6 mice, a strain with low predisposition for spontaneous skin tumors (http://www.informatics.jax.org/mtbwi/tumorFrequencyGrid.do).…”
Section: Resultsmentioning
confidence: 99%
“…B6 mice were from the Jackson Laboratory. Fhit − / − mice (~95% B6 genetic makeup) were generated as described 14, 26, backcrossed to B6 mice and carried as homozygous knockout mice; genotypes were confirmed before tumor induction. Mouse studies and experimentation were carried out according to protocols approved by the Ohio State University Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Another candidate is Nitrilase1 (Nit1), a highly conserved protein that functions as a tumor suppressor (Sun et al, 2009). In Arabidopsis, changes in the polymer structure and the intracellular localization of Nit1 are closely associated with the transition from proliferation to differentiation (Doskocilová et al, 2013).…”
Section: How Do Oxylipin Carbonyls Initiate Pcd?mentioning
confidence: 99%